Rejuvenating Smallholder Oil Palm Plantations: Challenges and Pathways To Sustainability - Judijanto, Loso (Jambura Agribusiness Journal, 2024)
Revitalizing oil palm smallholder plantations is crucial for improving yields and ensuring long-term sustainable development. Nevertheless, smallholders face numerous challenges, including limited financial resources, scarce access to essential inputs, and limitations in technical expertise. This research seeks to explore both the potential and the challenges associated with the renewal of smallholder oil palm plantations, focusing specifically on improvements in productivity and sustainable practices. A qualitative literature review approach was employed, synthesizing insights from prior academic studies, policy reports, and relevant publications. The analysis, conducted through thematic synthesis, highlights key factors influencing financial, technical, and environmental dimensions in the rejuvenation process. Findings indicate that while rejuvenation holds considerable promise for improving yields and advancing sustainable practices, persistent barriers remain, such as restricted financing options, inadequate technical capacity building, and environmental management concerns. However, smallholders involved in cooperative frameworks or sustainable supply chain initiatives tend to experience positive developments in both productivity and ecological outcomes. The study concludes that successful rejuvenation efforts demand a holistic strategy integrating financial support, technical assistance, and environmentally responsible farming methods. Further studies are suggested to investigate the prolonged socioeconomic effects of plantation rejuvenation and its contribution to strengthening ecological stability and participatory land management. By combining disparate findings from earlier research, this study offers a novel and integrative framework synthesis and suggests a new multidisciplinary framework to direct smallholder oil palm revival projects in a sustainable and repeatable manner.